Customer Satisfaction Mediated by Trust in Online Delivery Service “Gosend” - Theresye Yoanyta Octora; Marlina Iryatie; Adam Farrel Ghazali; Raka Adli Pribadi (Jurnal Ilmu Multidisiplin, 2025)
Gojek has become one of the solutions to facilitate urban mobility. In this research, the prominent phenomenon under investigation is various issues related to the delivery process, including timeliness of deliveries, compatibility of delivery locations with customer addresses, accuracy of delivery status, and any potential discourteous behavior that may occur on the part of the service providers in the customer context. The primary objective of this study is to examine the impact of service quality and perceived value on customer satisfaction levels, with trust as the mediator under scrutiny. This research adopts a quantitative approach, as population data is not available due to the total number of customers. A total of 100 respondents were selected using the SEM-PLS method. Data was collected through purposive sampling with specific criteria applied to the respondents. The results of this study indicate that service quality has a significant impact on customer trust, customer perceived value has an insignificant effect on customer trust, customer trust has a significant effect on customer satisfaction, service quality has an insignificant effect on customer satisfaction, and perceived value has a significant impact on customer satisfaction.